Algorithm for computing differential char sets efficiently - Cancan, Murat; Afzal, Farkhanda; Maqbool, Ayesha; Afzal, Deeba (Journal of discrete mathematical sciences & cryptography, 2020)
In order to triangularize differential polynomial sets and systems, we can use char sets method by Ritt and Wu. This method uses differential pseudo division for elimination of variables successively. In this paper, we have proved that Differential Pseudo division can be replaced by important reductions for computing differential char sets. An algorithm is presented for computing the differential char sets efficiently. This algorithmic scheme has been executed with precise admissible differential reductions. Primary results demonstrate that this new algorithm accomplishes better results than char set algorithm that are based on differential Pseudo division.